Pengaruh Organizational Justice terhadap Employee Engagement melalui Organizational Identification - Amelia Yuhana Prativi; Praptini Yulianti (Jurnal Maksipreneur, 2020)
This study uses objects in one of the state-owned companies engaged in microfinance services, namely PT. Investment Management. In this case, of course, PT PNM Investment Management has growth that is very dependent on the service of employees to customers. Therefore, companies must continually improve services to customers and be able to maintain and improve employee performance. This research aims to determine the effect of organizational justice on employee engagement through organizational identification. This quantitative study is based on data collected using a questionnaire distributed to 78 respondents of PT. Investment Management is then analyzed using partial least square. In the results of the analysis using PLS it was found that organizational identification was able to mediate the effect of organizational justice (distributive justice, procedural justice, interactional justice) on employee engagement. This shows that the employee engagement can be achieved by many factors and some of them are about the concept of justice applied by the company and identification of the organization owned by employees, especially employees of PT. PNM Investment Management.